Agro-Ecological Estimation of Various Fertilization Systems under Conditions of the Republic of Tatarstan - Adaev, N L; Zanilov, A Kh; Amaeva, A G; Khaziev, A Z; Adaev, I N; Khamzatova, M Kh; Israpilova, M A (KnE Life Sciences, 2019)
Producers of agricultural plants are increasingly marking a decrease in the responsiveness of cultivated plants to the mineral fertilizers applied to the soil. The explanation of this phenomenon can be the shift of limiting factors that determine the yield from mineral components in the soil to substances of organic and biological origin. The paper presents comparative data of the influence of mineral and organic fertilizer system on main biological indicators of the soil – nitrogen transforming groups of microorganisms, total microbial number (TMN), and soil respiration. The change in total and mineral nitrogen in the soil is estimated. The novelty of the study is that organic fertilizers are used in amounts comparable to the doses of mineral fertilizers in physical weight – 200 kg/ha. The application is carried out locally simultaneously with the seeding. As a result of the analysis, it has been found that ammonifiers (by 20.0–45 %), nitrifiers (by 30.0–46.7 %) numerically dominate in soil with organic fertilizers under all crops (corn, sunflower, soybean, sugar beet), the total microbial number is higher by 24.6–48.3 %. The intensity of carbon dioxide emissions (soil respiration) is also higher by 19.0–45.6 %. The intensity of biogeochemical processes in the soil and the related transformations of mineral nutrients, respectively and the provision of plants with them closely correlates with the number of valuable groups of microorganisms. The correlation coefficient between the number of ammonifiers and nitrifiers with the total nitrogen content in the soil under all studied crops in an organic fertilizer system is r=0.93.